Dielectric Properties of Natural Borneo Woods: Keranji, Kayu Malam, and Kumpang - Elammaran, Jayamani; Md Rezaur, Rahman; Sinin, Hamdan; Muhammad Idris, Kyari; Muhammad Khusairy, Bakri; Khairuddin, Sanaullah; Afrasyab, Khan (NC State University, 2020)
The dielectric behavior and properties of three types of Sarawak woods, under various conditions (untreated, alkaline treated, potassium carbonate treated, and heat treated), were investigated and discussed. The dielectric constant, loss, and dissipation factor tests were conducted via a dielectric impedance analyzer. The results revealed that the dielectric properties decreased in relation to an increase in frequency. With considerations to the treatment method, the highest dielectric constant values for the untreated samples were found in Kumpang wood, the highest dielectric constant values for the heat-treated samples and potassium carbonate treated samples were found in Keranji wood, and the highest dielectric constant values for sodium hydroxide treated samples were found in Kayu Malam wood. Therefore, it was evident that the physical properties, e.g., internal structure, density, moisture, temperature, etc., could affect the dielectric behavior and properties of the wood materials.